(untitled) (Scientific journal of the Fergana State University, 2024)
Research on hydrogen storage using carbon-based nanomaterials is currently attracting increasing interest. Yet, understanding the storage nature of graphene surfaces is still elusive. In this study, we investigated the physisorption mechanisms of H2 molecules on defective graphenes using reactive molecular dynamics simulations. We found that an increase in the size and concentration of defects in graphene increases the physisorption of H2 molecules on the surface due to a change in the partial charges of atoms in the system. Specifically, our results showed that in the case of the highest percentage of defects (10.27%), the gravimetric density of H2 molecules is about 2.12 wt.% at ambient conditions, which is within the range of gravimetric densities obtained from experiments and other simulations. The results also indicated that the physisorption of H2 molecules is related to both the size and the concentration of defects on the graphene surface. This study contributes to a better understanding of the mechanisms of hydrogen storage in graphene with various defects at the atomic level.